Experimental study of Polycyclic Aromatic Hydrocarbons (PAHs) in n-Heptane laminar diffusion flames from1.0 to 3.0 bar. (1st December 2017) - Zhou, Lei; Xiong, Gaihua; Zhang, Mengjie; Chen, Longfei; Ding, Shirun; de Goey, L.P.H.
Abstract: As PAHs (Polycyclic Aromatic Hydrocarbons) are the main precursor of soot formation during the combustion, the investigation of PAHs formation is essential for the understanding of the soot formation and soot reduction in combustion. In this study, a specially designed burner and the corresponding fueling system was used to stabilize a laminar diffusion flame of n-heptane up to 3.0 bar before it becomes unstable. Using the combination of LII (Laser Induced Incandescence) and LIF (Laser Induced Fluorescence) techniques, the PAHs and soot formation and their distributions in the studied flames were obtained and explained. The results showed that PAHs were almost surrounded by soot and were present in the lower part of the flame. Moreover, the integral soot and PAH intensities exhibited a power law dependence on the pressure, being proportional to p n with n of 1.38 ± 0.32 and 1.49 ± 0.25 respectively under the pressure range of 1.0–3.0 bar.